Pengaruh Biaya Penyelenggaraan Pendidikan Terhadap Minat Calon Mahasiswa Universitas Ibn Khaldun Bogor - Suharti, Titing; Nurhayati, Immas (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2015)
Educationis a matter thatshould be prioritizedinthemost importantaspects of lifein all sectors. Through education, people can developtheir own potentials. Within the framework ofglobalization, educationalpreparationnecessarysynergy withthe demands ofcompetition. Therefore, thedimensionof competitivenessinhuman resourceswould becomean importantfactorthatspurredthe effortsof humanresources qualitythrougheducation is ademandthatmust be put forward. To that end, the college is requiredto improvethe quality ofits graduatesthrough qualityeducationservices. Improving the quality ofeducationservicesis determinedby threefactors including: physicalpresenceasthe availability offacilities and infrastructure, qualityfaculty andstaffpersonnel, curriculum, information systems andthe costof education. Fatah(1998)statefunding of educationis a factor thatis unavoidablepresencein providingeducationalinputcomponents. Becauseeducation is aprocess, the inputqualitywillmakethequalityof teaching and learningprocessandin turnwillcreatebetterlearning outcomes. Correspondingly,Supriadi(2001) statedthat the costof educationis one component ofa veryimportantinputineducation.The costof educationis neededtofacilitatethe implementation ofschoolpolicies andprograms, implementation ofschoolactivities(intra andextra) andthe development ofthe institutionitself.Rising costsof educationshould bepositivelycorrelatedto the improvementof educationquality. The higher the qualityof education providedwill furtherenhance the imagein the eyes ofthe publicinstitutionswhich in turnwill furtherincrease the interestof society toUIKA The mainassumption of this study that educationhas economic valuein the formation ofhuman resources that need costadequately. The linkagebetween thefactorsof educationfinancingto the wishesorinterests of prospectivestudentswillbe the focusin this study. Research dataincludes fiveperiod/academicyearstartingfrom2007/2008up to2011/2012. The numberof dataobservationsare 79observationalstudies. Data processingis done usingthreeapproaches, namelymultiple linear regressionusingSPSSversion16.0, the priceelasticity ofdemandandtotalrevenue. Simplelinearregressionequationindicatesthat theincrease invariablecostsforanamountof educationcanlead to lowernumber ofnew admissionswho registerandfilereturnsforthose. ttestonslope, showingthe value ofthe test resultsarenot significantin explainingthe relationshipbetween thecoefficient ofImplementation education costto the amount of admission. Testing usinga regression modelwith an alfa 5%showednosignificant negativeeffectofchanges ineducation cost on the interest of new student orreceive thenull hypothesis. Based on correlationcoefficien, we can conclude that the influence of education cost to number ofnew admissions is veryweak. Coefficientof etermination(R Square) shows contribution education cost to number of new student is verylittle, just 0.003(or 0,3%) tothe number ofnew admissions. About 99,7%influencedby other factors. Based on thecalculation ofpriceelasticity ofdemand, the largestincrease ineducation costsin the yearin the academic year2011/2012in the amount of22.07% percentdecrease in the numberof studentsled toalow of-0,14%, meaning thatthere isinelastisdemandin the relationshipbetween the costof educationwithan interest ofUIKAstudentsBogor. Recommendationresultsusing thetwopreviousmodelsis reinforcedby thecalculation oftotalrevenue, whichincreasesthe cost of educationdoes notreduce the level ofearningsmanagementinstitutions.